The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.03.14.532528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanobodies against SARS-CoV-2 reduced virus load in the brain of challenged mice and neutralized Wuhan, Delta and Omicron Variants

Abstract: In this work, we developed llama-derived nanobodies (Nbs) directed to the receptor binding domain (RBD) and other domains of the Spike (S) protein of SARS-CoV-2. Nanobodies were selected after the biopanning of two Nb-libraries, one of which was generated after the immunization of a llama (lama glama) with the bovine coronavirus (BCoV) Mebus, and another with the full-length pre-fused locked S protein (S-2P) and the RBD from the SARS-CoV-2 Wuhan strain (WT). Most of the neutralizing Nbs selected with either RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…As shown in Figure c, the yeast-Nb33 achieved the highest signal response among these bioreceptors. According to the ELISA results from our collaborator, the Nb-33 achieved the lowest half-maximal effective concentration (EC 50 ) toward spike protein among the three nanobodies . This result indicated that Nb-33 has a higher capture efficiency and could be regarded as an ideal candidate for SARS-CoV-2 detection.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…As shown in Figure c, the yeast-Nb33 achieved the highest signal response among these bioreceptors. According to the ELISA results from our collaborator, the Nb-33 achieved the lowest half-maximal effective concentration (EC 50 ) toward spike protein among the three nanobodies . This result indicated that Nb-33 has a higher capture efficiency and could be regarded as an ideal candidate for SARS-CoV-2 detection.…”
Section: Resultsmentioning
confidence: 90%
“…According to the ELISA results from our collaborator, the Nb-33 achieved the lowest half-maximal effective concentration (EC 50 ) toward spike protein among the three nanobodies. 21 This result indicated that Nb-33 has a higher capture efficiency and could be regarded as an ideal candidate for SARS-CoV-2 detection. During culturing, yeast-Nb33 grew at the slowest rate, which might indicate there are more nanobodies expressed on the yeast surface.…”
Section: Determination Of Assay Conditionsmentioning
confidence: 87%
See 3 more Smart Citations